Cannabinoid Receptor Agonist Inhibits Atrial Electrical Remodeling in a Tachypaced Ex Vivo Rat Model - Lee, Danielle I.; Murninkas, Michael; Elyagon, Sigal; Etzion, Yoram; Anderson, Hope D. (Frontiers in Pharmacology, 2021)
Introduction: Atrial fibrillation (AF) leads to rate-dependent atrial changes collectively defined as atrial remodelling (AR). Shortening of the atrial effective refractory period (AERP) and increased conduction velocity are among the hallmarks of AR. Pharmacological strategies to inhibit AR, thereby reducing the self-perpetual nature of AF, are of great clinical value. Cannabinoid receptor (CBR) ligands may exert cardioprotective effects; CB13, a dual CBR agonist with limited brain penetration, protects cardiomyocytes from mitochondrial dysfunction induced by endothelin-1. Here, we examined the effects of CB13 on normal physiology of the rat heart and development of tachypacing-induced AR. Methods: Rat hearts were perfused in a Langendorff set-up with CB13 (1µM) or vehicle. Hemodynamic properties of non-paced hearts were examined conventionally. In a different set of hearts, programmed stimulation protocol was performed before and after atrial tachypacing for 90 min using a mini-hook platinum quadrupole electrode inserted on the right atrium. Atrial samples were further assessed by western blot analysis. Results: CB13 had no effects on basal hemodynamic properties. However, the compound inhibited tachypacing-induced shortening of the AERP. Protein expression of PGC1α was significantly increased by CB13 compared to vehicle in paced and non-paced hearts. Phosphorylation of AMPKα at residue threonine 172 was increased suggesting upregulation of mitochondrial biogenesis. Connexin43 was downregulated by tachypacing. This effect was diminished in the presence of CB13. Conclusions: Our findings support the notion that peripheral activation of CBR may be a new treatment strategy to prevent AR in patients suffering from AF, and therefore warrants further study